Acute pancreatitis in patients with pancreatic cancer: Timing of surgery and survival duration. Issue 3 (January 2017) - Li, Shaojun; Tian, Bole
Abstract : Abstract: Acute pancreatitis (AP) is a rare manifestation of pancreatic cancer (PC). The relationship between AP and PC remains less distinct. From January 2009 to November 2015, 47consecutive patients with PC who presented with AP were reviewed for this study. Clinical features, clinicopathologic variables, postoperative complications, and follow-up evaluations of patients were documented in detail from our database. In order to identify cutoff threshold time for surgery, receiver operating curve (ROC) was built according to patients with or without postoperative complications. Cumulative rate of survival was calculated by using the Kaplan–Meier method. The study was conducted in accordance with the principles of the Declaration of Helsinki and the guidelines of West China Hospital. This study included 35 men (74.5%) and 12 women (25.5%) (mean age: 52 years), with a median follow-up of 40 months. AP was clinically mild in 45 (95.7%) and severe in 2 (4.3%). The diagnosis of PC was delayed by 2 to 660 days (median 101 days). Thirty-nine (83.0%) cases underwent surgery. Eight (17.0%) cases performed biopsies only. Of 39 patients, radical surgery was performed in 32 (82.1%) cases and palliative in 7 (19.9%) cases. Two (8.0%) patients were needed for vascular resection and reconstruction. Postoperative complications occurred in 12 (30.8%) patients. About 24.5 days was the best cutoff point, with an area under curve (AUC) of 0.727 ( P  = 0.025, 95% confidence interval: 0.555–0.8999). The survival rate of patients at 1 year was 23.4%. The median survival in patients with vascular resection and reconstruction was 18 months, compared with 10 months in patients without vascular resection ( P  = 0.042). For the primary stage (T), Tix was identified in 3 patients, the survival of whom were 5, 28, 50 months, respectively. And 2 of them were still alive at the follow-up period. The severity of AP was mainly mild. Surgical intervention after 24.5 days may benefit for reducing postoperative complications. Patients with vascular resection and reconstruction, thus achieving tumor-free margins, had a long-time survival.